Controversies in the Technical Aspects of ACL Reconstruction : An Evidence-Based Medicine Approach - Nakamura, Norimasa; Zaffagnini, Stefano; Marx, Robert G.; Musahl, Volker (Springer Berlin Heidelberg : Imprint: Springer, 2017)
This book provides the reader with the best available evidence on the most pressing issues relating to reconstruction of the anterior cruciate ligament (ACL) with the goal of supporting surgical reconstruction of the ACL and improving outcomes for patients. Key topics for which evidence-based information is presented include selection of graft material and source, the use of different surgical techniques, graft rupture in relation to surgical technique, and progression to osteoarthritis. The book will aid the surgeon in making decisions with respect to fixation devices and tensioning, the bundles to be reconstructed, and whether to preserve remnants or partial bundle ruptures. An evidence-based stance is taken on evolving topics such as the anatomy of the tibial insertion site of the ACL and the role of the anterolateral capsule and posteromedial corner in high-grade rotatory instability. Furthermore, novel technical developments for measurement of knee laxity and soft tissue navigation are discussed. The reader will also find useful information on general issues concerning physical examination, arthroscopic setup, timing of reconstruction, anesthesia, and anticoagulation.
Keywords: Medicine.; Orthopedics.; Rehabilitation.; Sports medicine.; elektronické knihy; electronic books